Multinational Corporations - بعيرة, د. ابو بكر مصطفى (Dirasat in Economics and Business, 1982)
During the past few decades the volume of international trade has increased considerably. It went up from an estimated 57$ billion in 1950 to about $1507 billion in 1979. Both as a cause and a corollary of this emerged phenomenon of the Multinational corporations (MNC's). In 1980 Fortune magazine's 500 largest corporations reached $1650 billion in profits, and about 16 million people working for them (see table 1,2 and 3 of the main article in Arabic).